SOME EMOTIONS AND THEIR CAUSED FACTORS ON MOTORCYCLE RIDERS IN CONTRACTS (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2023)
The number of motorcycle vehicles in the city of Kediri in 2020 reached more than 280 thousand which was not matched by the development of facilities. This imbalance causes congestion on the Bandar Ngalim Bridge which connects the east-west side of the Brantas river. The purpose of this study was to analyze the psychological impact felt by drivers due to traffic jams. Data were collected by observing and interviewing students who were often stuck in traffic when they were about to leave for campus. Data analysis was carried out using qualitative analysis methods and presented in descriptive form. This research shows that drivers who are stuck in traffic jams tend to be emotional, namely angry and irritated, but some drivers are silent and do not mind the traffic jam. ABSTRAKJumlah kendaraan sepeda motor di Kota Kediri pada tahun 2020 mencapai lebih dari 280 ribu kendaraan yang tidak diimbangi dengan perkembangan fasilitas. Ketimpangan ini kerap menimbulkan kemacetan di Jembatan Bandar Ngalim yang menghubungkan sisi timur-barat sungai Brantas. Tujuan penelitian ini adalah menganalisis dampak psikologis yang dirasakan pengemudi akibat kemacetan lalu lintas. Pengumpulan data dilakukan dengan cara observasi dan wawancara terhadap mahasiswa yang sering terjebak kemacetan saat hendak berangkat ke kampus. Analisis data dilakukan dengan menggunakan metode analisis kualitatif dan disajikan dalam bentuk deskriptif. Penelitian ini menunjukkan bahwa pengemudi yang terjebak kemacetan cenderung emosional yaitu marah dan jengkel, namun ada pula pengemudi yang diam dan tidak mempermasalahkan kemacetan.